EVALUASI PROSES PRODUKSI IKAN CAKALANG ASAP (FUFU): KAJIAN TEKNOLOGI DAN DINAMIKA SOSIAL EKONOMI PEDESAAN DI DESA TAMBALA KAMPUNG BARU KABUPATEN MINAHASA - Merung, Arteurt Yoseph; Manuhutu, Ellia; Paendong, Stella Maria (Agripreneur : Jurnal Pertanian Agribisnis, 2025)
Skipjack tuna (Katsuwonus Pelamis) is one of Indonesia’s leading fishery commodities with high economic value.  However, due to its perishable nature, poper processing methods are required to extend its shelt life and increase added value.  This study aims to evaluate the production process of smoked Skipjack tuna (fufu) in tambala village, Minahasa by examining technological aspects and the socio-economic dynamic of bussines actors.  The research method is a quantitative approach, incorporating value-added analysis using the Hayami method and Swot Analysis. The research finding indicate that the effectiveness of smoking in the processing of smoked Skipjack tuna (fufu) is optimized at a smoking temperature of 80o – 100oC, wicth enhances both the shelf life and sensory quality of the product. Proper smoking effectiveness enables the production of split smoked Skipjack tuna (fufu) a value-added ratio of 25,70% (moderate category), which is higher than the whole smoked Skipjack tuna (fufu), which has only 13,15% (low category). The main challenges is this business include limited capital, raw material supply contrants, lack of innovation, and insufficient digital marketing.  Swot analysis show that this business has strengths in its strategic location and low production cost, as well as opportunities for increasing marked demand.  However, threats such as competition from similar products and fluctuation in raw material prices also exist.  The implication of this research include strategies for increasing added value, strengthening supply chains, accelerating digital marketing, development human resources and business and business regeneration, as well as policy recommendation and government support in terms of financial assistance and technology development.